Awareness and Practice on Prevention and Control of Dengue among Community People of Lalitpur Metropolitan City - K.C., Amita; Nepali, Sanjay (Journal of Advanced Academic Research, 2024)
Background: Dengue is a mosquito-borne viral disease that has rapidly spread in many countries worldwide in recent years. Dengue is a major public health problem in many countries. Dengue is a rapidly emerging disease in Nepal that is endemic across most provinces. The incidence of dengue has increased in recent years due to the expansion of the Aedes aegypti vector. The increasing outbreak of dengue in Nepal is becoming a major concern for the public health. Objective: The objective of the study was to assess awareness level and practice on prevention and control of dengue among community people in Lalitpur metropolitan city. Method: A community-based cross-sectional study was conducted from January to June 2023 at ten different wards in Lalitpur metropolitan city. Sample populations of 368 residents of Lalitpur metropolitan city above the age of 18 years were selected for the study. Simple random probability sampling technique used for the sample selection. Statistical Package for the Social Sciences (SPSS) 16 version used to analyze the data. Result: Majority (98.1%) of respondents knew about dengue fever. Most of the respondents (47.1%) answered that dengue is caused by aedes mosquito. Majority (71.4%) of respondents stated that dirty water was breeding sites of dengue mosquito. Primary preventive measures used were cleanliness 34.1 percent followed by use of mosquito net/coil 31.4 percent. The community people had good awareness (79.3%) of dengue, but poor practice (56.79%) in prevention and control of dengue. According to this study, socio-demographic factors such as age, sex, and education level were significantly linked to the knowledge level of the participants. Conclusion: According to this study, the community people had a good awareness level of dengue (79.3%). However, their practice of prevention and control of dengue was found to be poor (56.79%).